EVALUASI PROGRAM PEMERINTAH TENTANG HIV/AIDS DI KOTA PEKANBARU TAHUN 2012 - RIZKI ANANDA; Muhammad Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Based on the phenomenon in the implementation of government programs on HIV / AIDS is the responsibility of the Local Government Pekanbaru. For its implementation, local governments will delegate authority to the KPA Pekanbaru. While in charge is Deputy Mayor. Evaluation of programs implemented in Pekanbaru City Government with respect to the Program Counter is not running as it should. It is seen not sanggupnya government in response to the spread of HIV / AIDS in the city of Pekanbaru, even people with HIV / AIDS continues to increase every year. Thus, prevention programs can not be implemented that require evaluation in order to know the cause of this reduction programs can not reach the target.The purpose of this study was to determine and analyze Evaluation of Government Programs on HIV / AIDS in the city of Pekanbaru in 2012. Data obtained from respondents will be grouped by type, and then processed and presented in tabular form and then analyzed qualitatively and eventually will get conclusions about the results of the research.The results of the study concluded that the implementation of the program is the reduction of HIV / AIDS due to the limited amount of budgetary funds provided for the KPA limited so as not sufficient to carry out the work program primarily working in AIDS prevention programs in City Pekanbaru. Facilities and infrastructure lacking in the work program that caused the KPA is an independent institution which is not a government-owned institution. So the government needs to support the NAC effort in order to implement the program of work as are assigned. Solidaristas society lacking in addressing the problem of HIV / AIDS. Places that can cause infections such as AIDS where prostitution is still widely available in the city of Pekanbaru.Keywords: Evaluation, Government Programs, HIV / AIDS